Part Time Employment: The Australian Experience - Podbury, T; Andrews, L; Nuch, H; Abhayaratna, J (My University, 2008)
This staff working paper examines the extent and nature of part time work in Australia and how it has changed over time. It examines factors influencing decisions of firms and individuals to offer and accept part time work. It adds to the growing body of labour market research undertaken in the Productivity Commission.
Productivity Commission Staff Working Paper
Keywords: Employment -- Hours; Employment; Labour market; Employment and unemployment